Professor Algirdas Čižas as famous scientist and educator/Profesorius Algirdas Čižas - žymus mokslininkas ir pedagogas - Atkočiūnas, Juozas (Journal of Civil Engineering and Management, 1999)
Algirdas Eduardas ČIžas is Professor of the Department of Strength of Materials, Director of the Lithuanian Centre for Quality Assessment in Higher Education. Prof A. Čižas was born on September 16, 1929 in a picturesque Lithuanian locality, Anykščiai. In 1952 he graduated from Kaunas Polytechnic Institute (Faculty of Civil Engineering). In 1953–57 editor and head of the Division of Technical Literature in a publishing house in Vilnius, in 1959–64 editor of Lithuanian encyclopedias. In 1967 a Doctoral student, then teacher, Associated Professor, since 1977 full Professor at the Vilnius Civil Engineering Institute (later Vilnius Technical University). In 1980–87 Dean of Civil Engineering Faculty, since 1995 Director of the Centre for Quality. More than 100 scientific publications on higher education problems and structural mechanics, optimisation methods. A. Čižas has introduced restrictions of stiffness, influence of a cross-sectional shape and a strain-hardening factor into optimisation theory of structural mechanics. The first paper “Application of mathematical programming methods for analysis of elastic-plastic structures with restricted deformation” (in Russian) was published in “Statybine mechanika” (Structural mechanics) issued by the Kaunas Polytechnic Institute in 1966. A. Čižas reported his research results at international conferences in Russia, Poland, Italy, United Kingdom, USA, etc. More than 25 years of publishing “Lithuanian Proceedings in Mechanics” (“Lietuvos mechanikos rinkinys)” (1968–94) are related to the development of Lithuanian research in mechanics. During the whole period A. Čižas was a managing editor of the journal. All the papers in volumes 1–32 of the LPM were published in Russian with Lithuanian and English summaries. After integration of the journals, results of research on mechanics are published in “Mechanika” (Mechanics) and “Statyba” (Civil Engineering). A. Čižas is a member of editorial boards of both journals, an author of the textbook “Strength of Materials. Mechanics of Structural Members” (1993, in Lithuanian), a co-author of the textbook “Problems on Strength of Materials with Comments” (1985). He has translated (from Russian into Lithuanian) more than ten books. Prof A. Čižas is a coordinator of drafting several legislative acts for higher education. Member of the Seimas of Sqjūdis (1988–90), member of the Lithuanian State Language Committee at the Seimas of the Republic of Lithuania, expert of Science Council of Lithuania. Article in Lithuanian. First Published Online: 26 Jul 2012